2021
DOI: 10.1111/dth.14727
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of selected angiogenesis markers in the serum of middle‐aged male patients with plaque psoriasis

Abstract: Local angiogenesis accompanies inflammation in psoriasis‐affected skin. To determine the serum concentrations of selected pro‐ and anti‐angiogenic factors and their interrelationships in patients with plaque psoriasis. The study included 41 men diagnosed with psoriasis, aged 43.5 ± 11.7 years. The Psoriasis Area and Severity Index score was 23.4 ± 5.2 points. The control group consisted of 38 healthy, age‐matched men. The levels of pro‐angiogenic cytokines and angiogenesis inhibitors, including fibroblast grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“… 19 , 20 Studies showed VEGF is up‐regulated in the psoriatic lesions and serum and VEGF expression is positively related to the severity of psoriasis. 21 , 22 , 23 , 24 In our study, we confirmed the level of VEGF is elevated in mice psoriatic skin tissues. We found that C10orf99 knockdown could reduce IMQ‐induced VEGF expression in mice.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“… 19 , 20 Studies showed VEGF is up‐regulated in the psoriatic lesions and serum and VEGF expression is positively related to the severity of psoriasis. 21 , 22 , 23 , 24 In our study, we confirmed the level of VEGF is elevated in mice psoriatic skin tissues. We found that C10orf99 knockdown could reduce IMQ‐induced VEGF expression in mice.…”
Section: Discussionsupporting
confidence: 83%
“…VEGF is the most important proangiogenic factor and it's role in angiogenesis has been well known 19,20 . Studies showed VEGF is up‐regulated in the psoriatic lesions and serum and VEGF expression is positively related to the severity of psoriasis 21–24 . In our study, we confirmed the level of VEGF is elevated in mice psoriatic skin tissues.…”
Section: Discussionsupporting
confidence: 79%
“…[16][17][18][19] Patients with psoriasis also have increased plasma levels of VEGF-A, which correlate with disease severity. 16,[20][21][22] The emergence of biologic therapy over the last two decades 23 has shifted psoriasis management from treatment with conventional systemic treatments (methotrexate, oral retinoids and ciclosporin) to those which target key cytokines in the inflammatory pathways involved in psoriasis [e.g. tumour necrosis factor (TNF)-a, interleukin (IL)-23 or IL-17A].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of VEGF‐A, which binds to VEGF‐A receptor‐1 (VEGFR‐1) and VEGFR‐2, 15 is increased within plaques of psoriasis compared with nonlesional skin (Figure 1). 16–19 Patients with psoriasis also have increased plasma levels of VEGF‐A, which correlate with disease severity 16,20–22 …”
Section: Figurementioning
confidence: 99%
“…Plasma levels of VEGF-A are higher in patients with psoriasis than in healthy individuals, and they correlate with disease severity [ 31 , 32 ]. VEGF-A is produced principally by activated keratinocytes in the skin of patients with psoriasis [ 29 , 33 , 43 ]. Other VEGFs (not produced by keratinocytes) are synthesized by fibroblasts [ 29 ] and immune cells such as mast cells [ 34 , 35 ].…”
Section: Psoriasismentioning
confidence: 99%